Wandering monuments in the space of Slupsk (before and after World War II) - Krawiec-Złotkowska, Krystyna (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The chapter presents monuments (denkmals) existing in Slupsk before World War II and monuments, which replaced them after 1945. Attention was also paid to pre-war objects, which changed their original location after the war (e.g. the memorial to the victims of the Franco-Prussian war, the sculpture Humiliated, fragments of German tombstones and Jewish matzevot). On the example of monuments, there is presented an outline of the post-war historical policy applied to the existing cultural heritage of the Western and Northern Territories. A manifestation of this policy was destroying the signs of a foreign culture or ignoring it and changing semantics. It was noticed that the cultural shift made after the transformation of 1989 and the abolition of censorship in 1990 in Poland, played an important role in the treatment of foreign heritage. Monuments in Slupsk are presented in the context of the theory of places of remembrance, culture of remembrance, historical politics, history in public space and the existing ”difficult heritage”. Their fate in the city ”with exchanged blood” reveals a strategy of rejecting or assimilating foreign heritage, and at the same time prompts reflection on the past and the future.